Construction of haemodialysis nursing‐sensitive quality indicators based on Donabedian theory: A Delphi method study - Lin Chen; Yingjun Zhang; Chao Li; Qiao Li; Li He (Wiley, 2023)
Abstract Aims To establish a sensitive, scientific and practical evaluation system for haemodialysis nursing and to provide a reference for the evaluation of haemodialysis nursing quality. Design Through a literature review and Delphi method. Method According to the literature review, a preliminary nursing‐sensitive quality indicators for haemodialysis were established, and an expert survey questionnaire was designed. Finally, the evaluation system for the nursing‐sensitive quality indicators was determined using the Delphi method. Results Thirteen nursing‐sensitive quality indicators for haemodialysis were finally constructed, including two structural indicators, three process indicators and eight outcome indicators. The effective recovery rate of the two rounds of expert survey questionnaires was 100%, the coefficient of judgement basis is 0.956, the coefficient of familiarity is 0.833, the coefficient of authority is 0.895, and the Kendall's harmony coefficients of the two rounds of expert consultation were 0.158 ~ 0.307 and 0.170 ~ 0.315, respectively, with statistical significance (p < .05). Clinical relevance In this study, the nursing‐sensitive quality indicators for haemodialysis were developed by the Delphi method and included structural indicators, outcome indicators and process indicators, which made up for some deficiencies noted in previous studies. The authors have provided a more reliable and comprehensive basis for evaluating the quality and safety of haemodialysis nursing in the future.